DAMPAK REFORMASI BIROKRASI (Studi Tentang Restrukturisasi di Dinas Sosial Provinsi Sulawesi Utara) - WARDANA, ALYA FAUZIAH; RARES, JOYCE; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2021)
The Bureaucratic Structure Reform Policy aims to streamline the existing structure, in this case it aims tostrengthen strategic functions that were not previously accommodated and accommodated by the newstructure and increase public satisfaction with the performance and services of the North SulawesiProvincial Social Service. However, these hopes have not been maximally achieved. Therefore, this studyis proposed to answer questions about the Impact of the Bureaucratic Structure Reform Policy in theSocial Service of North Sulawesi Province. In this study, using the policy impact theory from JamesAnderson, the impact of policy can be seen based on 5 dimensions that can be used as a benchmark.Expected policy impact (intended consequences). Policies may have an impact on situations or groupsbeyond the target or purpose of the policy being made. The impact of the policy is likely to have an impacton current and future circumstances. The impact on direct costs, direct costs speak of the direct costsincurred to finance public policy programs. Policies may also have indirect costs that are borne by societyor some members of society as a result of public policies, for example regarding anxiety, discomfort, costsof social chaos, satisfaction, or even aesthetic costs. In this study, using a qualitative descriptive researchmethod, namely through interviews with 8 informants in direct observation, and looking for documentsrelated to policy, assisted by recording devices and writing instruments. The results of this study generallyexplain that the impact of this Bureaucratic Structure Reform policy has not fully achieved the expectedresults.Keywords : Policy Impact, Bureaucratic Structure Reform.